ANALYSIS OF FACTORS AFFECTING RICE IMPORTS IN NORTH SUMATRA IN 1998-2020 - Sarma Punia Manullang; Ermi Tety; susy edwina (Indonesian Journal of Agricultural Economics, 2023)
North Sumatra is one of the rice-producing provinces in Indonesia. Although North Sumatra is rice producing center in Indonesia, North Sumatra still continues to import rice to keep the rice needs of the population and the government's rice reserves. This study aims to: (1) Analyzed the conditions of foreign trade related to North Sumatra's imports of rice commodities in 1998-2020. (2) Analyze the effect of rice production, rice consumption, import tariffs, Rupiah exchange rate against USD and inflation on rice imports in North Sumatra province. (3) Analyze which independent variables most influence rice imports in North Sumatra. The data used are secondary data sourced from BPS North Sumatra, the Worldbank Website, Bank Indonesia, the Ministry of Finance and other agencies that provide data related to this research. The data taken are data on imported rice, rice production, rice consumption, exchange rates, and inflation in North Sumatra in time series from 1998-2020. Data analysis was performed using multiple linear regression analysis using the Ordinary Least Square (OLS) method and using the SPSS 24 program. The results of this study Simultaneously show that the independent variables jointly have a significant effect on rice imports. And partially the variables of production, exchange rates, and inflation have negative and not significant effect on rice imports, the rice consumptions variable has a positive and not significant effect on rice imports, and the import tariff variable has a negative and significant effect on rice imports in North Sumatra and the most effected variable on rice import is import tariff